2012
DOI: 10.1186/1471-2180-12-96
|View full text |Cite
|
Sign up to set email alerts
|

Detection of mixed populations of wild-type and YMDD hepatitis B variants by pyrosequencing in acutely and chronically infected patients

Abstract: BackgroundLamivudine (LAM) is associated with the highest known rate of resistance mutations among nucleotide analogs used to treat chronic hepatitis B virus (HBV) infection. Despite this, LAM continues in widespread use, especially in combination therapies. The primary LAM resistance mutation (rtM204V/I) occurs in the YMDD motif of HBV polymerase. The aim of this study was to characterize Brazilian HBV isolates from acute and chronic cases by direct sequencing, and to identify HBV quasispecies in the YMDD mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…UDPS has been used to assess the preexistence of HBV variants resistant to nucleoside/nucleotide analogs in a few studies. However, these works suffered from important methodological flaws, including lack of sensitivity, no consideration of the error rate of the method to establish reliable cutoffs and ensure specificity, too‐short genomic region analyzed, and/or no linkage studies …”
Section: Discussionmentioning
confidence: 99%
“…UDPS has been used to assess the preexistence of HBV variants resistant to nucleoside/nucleotide analogs in a few studies. However, these works suffered from important methodological flaws, including lack of sensitivity, no consideration of the error rate of the method to establish reliable cutoffs and ensure specificity, too‐short genomic region analyzed, and/or no linkage studies …”
Section: Discussionmentioning
confidence: 99%
“…The second two substitutions were not found in the current cohort.The current hypothesis is that interactions between residues at position 204 and those at 184, 202 or 250 are important for a functional HBV RT enzyme, or perhaps that the LVDr, ADVr and/or both substitutions further decrease the replication capacity of the more impaired M204I virus to below levels required to survive. Recently, lots of reports have demonstrated that YMDD motif mutations can naturally occur in chronic HBV patients without antiviral theraphy (Ağca et al, 2012;Lee et al, 2012;Mello et al, 2012;Tan et al, 2012;Wu et al, 2012). Li et al(2013) have claimed that HBV-related HCC patients with YMDD motif mutations have no response to lamivudine therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The techniques that have been applied for the direct detection of MRMP include PCR followed by Sanger sequencing (11,14,16), pyrosequencing (17,18), high-resolution melting curve analysis (19)(20)(21), allele-specific PCR (22), and PCRrestriction fragment length polymorphism (23). In the context of viral infections, natural occurrences of mixed drug-sensitive and -resistant subpopulations are well documented (24)(25)(26)(27)(28). The enrichment of minor resistant subpopulations has further been demonstrated to be associated with antiviral treatment failure (25,26).…”
mentioning
confidence: 99%
“…In the context of viral infections, natural occurrences of mixed drug-sensitive and -resistant subpopulations are well documented (24)(25)(26)(27)(28). The enrichment of minor resistant subpopulations has further been demonstrated to be associated with antiviral treatment failure (25,26). This has led to the term "quasispecies," which has been used widely to describe sequence variants in heterogeneous virus populations (25,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation